Solvent-free synthesis of dibenzo[b, j][1, 10]phenanthroline derivatives using Eaton's reagent as catalyst. Issue 10 (19th May 2017) - Satheeshkumar, Rajendran; Rajendra Prasad, Karnam Jayarampillai
ABSTRACT: A new class of dibenzo[ b, j ][1, 10]phenanthrolines has been prepared. The synthon acridones were achieved in very good yield by a one-pot reaction of 2-amino-5-chloro or 2′-chloro/flouro-substituted benzophenones with 1, 2-cyclohexanedione in the presence of freshly prepared Eaton's reagent (phosphorus pentoxide–methanesulfonic acid) without solvent, through Friedländer synthesis. Then these intermediates were reacted with 2-amino-3, 5-dibromobenzaldehyde to afford 1, 3-dibromo-10-chloro-8-aryl-6, 7-dihydrodibenzo[ b, j ][1, 10]phenanthroline. Also an one-pot reaction between 2 mol of 2-amino-5-chloro aryl benzophenones with 1 mol of 1, 2-cyclohexanedione to get 3, 10-dichloro-5, 8-diaryl-6, 7-dihydrodibenzo[ b, j ][1, 10]phenanthroline has also been reported. The newly synthesized structures of the compounds were deduced by spectroscopic techniques. GRAPHICAL ABSTRACT: